Penyuluhan hukum kenakalan remaja dalam perspektif hukum serta pencegahannya pada SMA Harapan Mekar - Suwanto Suwanto; Firmansyah Firmansyah; Abdul Halil; Muhammad Koginta Lubis; Junaidi Lubis (Nur Science Institute, 2026)
Adolescence is a developmental phase that is particularly vulnerable to deviant behavior. The rising incidence of student misconduct, such as school fights, drug misuse, and risky sexual behavior, underscores the need to strengthen legal awareness early to safeguard young people’s futures. This legal outreach program at SMA Harapan Mekar, Medan, aimed to provide legal education for Grade 12 students (35 participants) on the boundaries of juvenile delinquency that may escalate into criminal offenses and the related legal consequences under the Indonesian Criminal Code (KUHP). The program employed interactive lectures, small-group discussions, and analysis of real-life cases involving adolescents. The results indicate increased student legal awareness, reflected in participants’ ability to identify forms of delinquency that may lead to legal problems and to understand the potential criminal sanctions that may be imposed. The program emphasizes prevention through character strengthening within the school environment. Sustaining its impact requires collaboration among law enforcement, academics, and schools to foster a law-abiding, legally aware generation.